Declining old‐forest species as a legacy of large trees lost. Issue 3 (5th December 2017) - Jones, Gavin M.; Keane, John J.; Gutiérrez, R. J.; Peery, M. Zachariah
Abstract: Aim: Global declines in large old trees from selective logging have degraded old‐forest ecosystems, which could lead to delayed declines or losses of old‐forest‐associated wildlife populations (i.e., extinction debt). We applied the declining population paradigm and explored potential evidence for extinction debt in an old‐forest dependent species across landscapes with different histories of large tree logging. Location: Montane forests of the Sierra Nevada, California, USA. Methods: We tested hypotheses about the influence of forest structure on territory extinction dynamics of the spotted owl ( Strix occidentalis ) using detection/non‐detection data from 1993 to 2011 across two land tenures: national forests, which experienced extensive large tree logging over the past century, and national parks, which did not. Results: Large tree/high canopy cover forest was the best predictor of extinction rates and explained 26%–77% of model deviance. Owl territories with more large tree/high canopy cover forest had lower extinction rates, and this forest type was ~4 times more prevalent within owl territories in national parks ( x ¯  = 19% of territory) than national forests ( x ¯  = 4% of territory). As such, predicted extinction probability for an average owl territory was ~2.5 times greater in national forests than national parks, where occupancy was declining ( λ ¯ ^ < 1 ) and stable ( λ ¯ ^ = 1 ), respectively. Large tree/high canopy cover forest remained consistently low, but did not decline, during the study period on national forests while owl declines were ongoing—an observation consistent with an extinction debt. Main conclusions: In identifying a linkage between large trees and spotted owl dynamics at a regional scale, we provide evidence suggesting past logging of large old trees may have contributed to contemporary declines in an old‐forest species. Strengthening protections for remaining large old trees and promoting their recruitment in the future will be critical for biodiversity conservation in the world's forests.